Human milk banks in the response to COVID-19: a statement of the regional human milk bank network for Southeast Asia and beyond - Estrella Olonan-Jusi; Paul G. Zambrano; Vu H. Duong; Nguyen T. T. Anh; Nant S. S. Aye; Mei Chien Chua; Hikmah Kurniasari; Zaw Win Moe; Sopapan Ngerncham; Nguyen T. T. Phuong; Janice Datu-Sanguyo (BMC, 2021)
Abstract Background The World Health Organization (WHO) recommendations on infant feeding in the context of COVID-19 uphold standing recommendations for breastfeeding, non-separation, and skin-to-skin contact, including the use of donor human milk when mother's own milk is not available. Insufficient guidance on the use of donor human milk and the role of human milk banks in the pandemic response COVID-19 clinical management guidelines in seven countries in Southeast Asia are not aligned with WHO recommendations despite the lack of evidence of transmission through either breastmilk or breastfeeding. The use of safe donor human milk accessed through human milk banks is also insufficiently recommended, even in countries with an existing human milk bank, leading to a gap in evidence-based management of COVID-19. This highlights long-standing challenges as well as opportunities in the safe, equitable, and resilient implementation of human milk banks in the region. Conclusions This statement reflects the expert opinion of the Regional Human Milk Bank Network for Southeast Asia and Beyond on the need to revisit national guidelines based on the best evidence for breastfeeding during the COVID-19 pandemic, to incorporate human milk bank services in national obstetric and newborn care guidelines for COVID-19 where possible, and to ensure that operations of human milk banks are adapted to meet the needs of the current pandemic and to sustain donor human milk supply in the long-term. The Network also recommends sustained engagement with the global human milk bank community.